THE FORTUNE TELLER IS ONE OF THE HUMOROUS CHARACTERS IN COMICS (Scientific journal of the Fergana State University, 2023)
The article examines the images of a fortune-teller, romchi as one of the traditional humorous images of works in a humorous spirit.